PENGARUH PERBEDAAN SUHU TERHADAP KELANGSUNGAN HIDUP DAN PERTUMBUHAN IKAN TAPAH (Wallago leeri) PADA TAHAP DOMESTIKASI - Yogie Purnama Hadi; Usman M Tang; Mulyadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted on February-April 2015 in Hatchery on Jl.Taman Karya, Pekanbaru-Riau Province. The purpose of this research is to knowthe influence of temperature for survival rate and growth of Tapah (Wallagoleeri). The method used a experimental with design used Randomized DesignComplete (RAL) with 3 (three) treatment temperatures of 27, 29 and 31oC and 4(four) replicated. The result has shown that the temperature directly influence forsurvival rate and growth of Tapah (Wallago leeri) with significant value(0,00)<(0,05). The best treatment were obtained in 29oC provides the values dailyweight rate is 1,21% and survival rate 100%.Keywords : Wallago leeri, Temperature, Survival rate, Growth